2022
DOI: 10.1146/annurev-neuro-110920-040422
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Mechanisms Regulating Mood State Transitions in Depression

Abstract: Depression is an episodic form of mental illness characterized by mood state transitions with poorly understood neurobiological mechanisms. Antidepressants reverse the effects of stress and depression on synapse function, enhancing neurotransmission, increasing plasticity, and generating new synapses in stress-sensitive brain regions. These properties are shared to varying degrees by all known antidepressants, suggesting that synaptic remodeling could play a key role in depression pathophysiology and antidepre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 159 publications
3
24
0
1
Order By: Relevance
“…Ketamine is primarily an NMDAR antagonist and therefore has direct action on glutamatergic receptors in the brain. There is a growing consensus that the therapeutic effects of ketamine depend critically on its influence on glutamatergic signaling. By contrast, psychedelics such as psilocybin are serotonin receptor agonists, and therefore studies of the drugs’ effect on neural plasticity have mostly focused on the pharmacology of serotonin. , The exploratory analyses in this study revealed a correlation between Htr2a transcript levels and psilocybin-evoked c-Fos expression, consistent with the known receptor interaction. However, we also observed robust relationships for glutamatergic receptors including Grin2a and Grin2b , particularly for cortical regions, which means that the presence of glutamatergic receptors is an even stronger indicator for whether a cortical region is sensitive to psilocybin-evoked neural plasticity.…”
Section: Discussionsupporting
confidence: 67%
“…Ketamine is primarily an NMDAR antagonist and therefore has direct action on glutamatergic receptors in the brain. There is a growing consensus that the therapeutic effects of ketamine depend critically on its influence on glutamatergic signaling. By contrast, psychedelics such as psilocybin are serotonin receptor agonists, and therefore studies of the drugs’ effect on neural plasticity have mostly focused on the pharmacology of serotonin. , The exploratory analyses in this study revealed a correlation between Htr2a transcript levels and psilocybin-evoked c-Fos expression, consistent with the known receptor interaction. However, we also observed robust relationships for glutamatergic receptors including Grin2a and Grin2b , particularly for cortical regions, which means that the presence of glutamatergic receptors is an even stronger indicator for whether a cortical region is sensitive to psilocybin-evoked neural plasticity.…”
Section: Discussionsupporting
confidence: 67%
“…Ketamine is primarily a NMDAR antagonist, and therefore has direct action on glutamatergic receptors in the brain. There is growing consensus that the therapeutic effects of ketamine depend critically on its influence on glutamatergic signaling [69][70][71][72] . By contrast, psychedelics such as psilocybin are serotonin receptor agonists, and therefore studies of the drugs' effect on neural plasticity have mostly focused on the pharmacology of serotonin [12][13][14]64 .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that resveratrol administration can improve anxiety-like behavior and reduce the increase of dendritic spines in the NAc induced by social isolation, suggesting that resveratrol plays a region-specific regulatory effect on dendritic spines. Moreover, many studies have shown that the regulatory effect of stress on synaptic remodeling is different in brain regions [ 48 ]. It was reported that the number and morphology of spines are connected to synaptic plasticity and circuit remodeling in the NAc [ 12 ].…”
Section: Discussionmentioning
confidence: 99%